2005
DOI: 10.1242/jcs.02328
|View full text |Cite
|
Sign up to set email alerts
|

Cellular invasion byStaphylococcus aureusreveals a functional link between focal adhesion kinase and cortactin in integrin-mediated internalisation

Abstract: Nosocomial infections by Staphylococcus aureus, a Gram-positive pathogen colonising human skin and mucosal surfaces, are an increasing health care problem. Clinical isolates almost invariably express fibronectin-binding proteins that, by indirectly linking the bacteria with host integrin α5β1, can promote uptake of the microorganisms by eukaryotic cells. Integrin engagement by pathogenic fibronectin-binding S. aureus, but not by non-pathogenic S. carnosus, triggered the recruitment of focal contact-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(177 citation statements)
references
References 66 publications
6
166
2
Order By: Relevance
“…Because it has been shown that c-Src is the major tyrosine kinase that phosphorylates Cas (Astier et al, 1997;Ruest et al, 2001;Agerer et al, 2005), we assayed Salmonella internalization in cells treated cells with a Src inhibitor, PP2. Although PP2 treatment efficiently inhibited tyrosine phosphorylation of Cas during Salmonella invasion (see Supplementary Material, Figure S3), bacterial internalization remained unaffected under these conditions ( Figure 6B).…”
Section: Cas Is Required For Salmonella Invasionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because it has been shown that c-Src is the major tyrosine kinase that phosphorylates Cas (Astier et al, 1997;Ruest et al, 2001;Agerer et al, 2005), we assayed Salmonella internalization in cells treated cells with a Src inhibitor, PP2. Although PP2 treatment efficiently inhibited tyrosine phosphorylation of Cas during Salmonella invasion (see Supplementary Material, Figure S3), bacterial internalization remained unaffected under these conditions ( Figure 6B).…”
Section: Cas Is Required For Salmonella Invasionmentioning
confidence: 99%
“…Similarly, uptake of Yersinia upon invasin-mediated engagement of ␤ 1 integrin and Streptococcus via fibronectin-binding integrins is dependent on FAK (Alrutz and Isberg, 1998;Ozeri et al, 2001;Bruce-Staskal et al, 2002). More recently, Agerer et al (2005) showed that FAK plays an essential role in integrin ␣ 1 ␤ 5 -mediated invasion of Staphylococcus. However, each of these processes is accompanied by increased tyrosine phosphorylation of FAK, indicative of its activation during particle internalization.…”
Section: Overexpression Of Fak Rescues Salmonella Internalization In Casmentioning
confidence: 99%
See 2 more Smart Citations
“…In other cases, the bacteria use an indirect route by engaging cell surface receptors coupled to the cytoskeleton including integrins, cadherins or immunoglobulin-related cell adhesion molecules (Hauck, 2002). For example, S. flexneri as well as S. aureus are able to connect to cell surface integrins to trigger actin-dependent internalization (Watarai et al, 1996;Sinha et al, 1999;Agerer et al, 2005). Listeria monocytogenes targets host E-cadherin by means of the InlA protein to enter epithelial cells (Mengaud et al, 1996;Lecuit et al, 1999).…”
Section: Introductionmentioning
confidence: 99%